Analysis of Four CommunityBased Entrepreneurships in Rural Water Supply in Bogor - Santi Susanti (International Journal of Family Business Practices, 2018)
Local water supply based on community development were built by using funding from Local government. Accountability of this funding for local community entrepreneurship is debatable. This paper will explain how local water community entrepreneurship in Bogor can be determined in four community-based: aspect of infrastructure, training of human resources, revenue collection, and post  onstruction support. The rural water supply in Bogor were studied by combining quantitative and qualitative methods. The study provides evidence on the need todesign policies and programs that provide sustainable services in Community-BasedEntrepreneurship.